2014
DOI: 10.1111/bjd.13139
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of response in patients with moderate-to-severe psoriasis treated with etanercept

Abstract: Etanercept treatment-response appears to occur in a body- and component-specific manner. Changes in quality of life are not captured by PASI or its subscales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…Griffiths and colleagues reported weak to moderate correlations between DLQI and PASI total scores and noted that changes in QoL do not appear to be captured by PASI or its subscales. We confirm this assumption, highlighting the role of patient‐assessed psoriasis symptoms on top of PASI in affecting HRQoL and work productivity and activity impairment outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Griffiths and colleagues reported weak to moderate correlations between DLQI and PASI total scores and noted that changes in QoL do not appear to be captured by PASI or its subscales. We confirm this assumption, highlighting the role of patient‐assessed psoriasis symptoms on top of PASI in affecting HRQoL and work productivity and activity impairment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The Dermatology Life Quality Index (DLQI) is the most commonly used instrument to assess the health‐related quality of life (HRQoL) of patients with psoriasis . However, increasing evidence confirms only weak to moderate correlations between the PASI and DLQI . This suggests that factors other than objective disease severity may play a role in patients’ evaluations of their HRQoL.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical practice, physicians focus on elements of the PASI (e.g., size and appearance of lesions), whereas patients tend to focus on the location of lesions and impact of the disease on their lives. The correlation between improvements in psoriasis lesions (as measured by PASI) and improvements in quality of life (as measured by DLQI) varies, with some studies showing weak correlations [16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, as well as in clinical practice, it has been observed that biologic treatment response typically starts on the head and upper body and progresses downward to lower body regions and extremities [13, 14]. For example, after 16 weeks of treatment with the tumor necrosis factor-alpha inhibitor adalimumab, the greatest PASI 100 subscore response rates were reported on the head and neck (55.7%) and the trunk (49.1%) compared with the upper limbs (33.3%) and the lower limbs (30.6%) [14].…”
Section: Discussionmentioning
confidence: 99%